CORS (CROM20): A new high‐prevalence antigen in the Cromer blood group system. Issue 11 (8th September 2020) - Vrignaud, Cédric; Chiaroni, Jacques; Durieux‐Roussel, Elisabeth; Le Van Kim, Caroline; Azouzi, Slim; Peyrard, Thierry
Abstract: The Cromer blood group system consists of 19 antigens (16 of high prevalence and 3 of low prevalence). This study describes the identification and characterization of a new Cromer high‐prevalence antigen, named CORS. The CORS‐negative proband carries a c.713G>A substitution in the CD55 gene, resulting in the substitution of glycine 238 into a glutamic acid (p.Gly238Glu).